Efecto de la incorporación de silicato de magnesio en la fertilización mineral del cultivo de maíz (Zea Mays L.) en Finca La Vega, San Carlos - Sancho-Mora, Andrés (Instituto Tecnológico de Costa Rica, 2016)
The following research addresses, as main objective the effects of the inclusion of magnesium silicate on the mineral fertilization of the cultivation of corn. This research was done in Finca La Vega, belonging of the Tecnológico de Costa Rica in Florencia, San Carlos; which soil is from an inceptisol order, whit medium fertility and claylom texture. For the development of the research were used five treatments, with five repetitions each in order to reach a total of twenty-five experimental units, which were established within an area of 992,2 m2, using a completely random experimental design. The variables evaluated were of the plant’s height, number of leaves, dry weight of the plant, length of the corn cob, weight of the corn cob, weight of a 1000 grains and the yield of grains; whose data were subjected to an analysis of variance and to a comparison of contrasts between the different treatments. The results obtained showed non-significant differences (p-value ˃ 0.05), for most variables evaluated, except for the dry weight of the plant and length of the corn cob, in which significant differences (p-value ˂ 0.05) were presented by incorporating magnesium silicate in mineral fertilization; however, the observed effect is attributed to the magnesium component (MgO), discarding the possible effect of silicon (SiO2) on the evaluated variables. Furthermore, it could not be determined whether the incorporation of magnesium silicate can influence the reduction of the phosphorus (P2O5) in the fertilization of the corn crop.
Trabajo Final de Graduación (Licenciatura en Ingeniería en Agronomía). Instituto Tecnológico de Costa Rica, Escuela de Agronomía, 2016.
Keywords: Producción agrícola; Fertilización; Cultivo de maíz; Propiedades químicas; Suelo; Nutrición de las plantas; Silicatos magnésicos; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Agronomy